2018
DOI: 10.1093/jnci/djy004
|View full text |Cite
|
Sign up to set email alerts
|

The Heterogeneity Between Lynch-Associated and Sporadic MMR Deficiency in Colorectal Cancers

Abstract: There are heterogeneities in dMMR CRCs. Lynch-associated dMMR patients present with more somatic mutations and neoantigens compared with sporadic dMMR, which probably results in stronger immunoreactions and survival improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 40 publications
9
29
0
Order By: Relevance
“…Standardized postoperative monitoring and follow-ups enabled us to detect these metachronous tumors at earlier stages, most of which were cured after complete resection. OS is the most important indicator for evaluating long-term prognosis, and the current study con rms what many studies have already proposed, that LS patients have better long-term prognosis than SCRC patients [7][8][9][10][11][12][13][14][15][16][17].The current study has con rmed that apart from factors intrinsic to the initial primary tumor, such as tumor characteristics, pathological type, and differentiation grade, tumor progression such as recurrence and metastasis is independent prognostic factor affecting long-term survival. Thus, given that microsatellite instability (MSI) tumors experience lower rates of local tumor recurrence, especially at distant sites, than do microsatellite-stable (MSS) tumors [24].CRC displaying MSI that are diagnosed at early stages have a better prognosis compared to CRC displaying MSS [24].…”
Section: Discussionsupporting
confidence: 85%
“…Standardized postoperative monitoring and follow-ups enabled us to detect these metachronous tumors at earlier stages, most of which were cured after complete resection. OS is the most important indicator for evaluating long-term prognosis, and the current study con rms what many studies have already proposed, that LS patients have better long-term prognosis than SCRC patients [7][8][9][10][11][12][13][14][15][16][17].The current study has con rmed that apart from factors intrinsic to the initial primary tumor, such as tumor characteristics, pathological type, and differentiation grade, tumor progression such as recurrence and metastasis is independent prognostic factor affecting long-term survival. Thus, given that microsatellite instability (MSI) tumors experience lower rates of local tumor recurrence, especially at distant sites, than do microsatellite-stable (MSS) tumors [24].CRC displaying MSI that are diagnosed at early stages have a better prognosis compared to CRC displaying MSS [24].…”
Section: Discussionsupporting
confidence: 85%
“…A number of factors could underlie inter-tumoral heterogeneity of TILs among dMMR tumors including differences in the overall mutation burden, unstable microsatellites, or variability in neoantigen profiles (36). A recent study found that MSI CRCs from patients with Lynch Syndrome (n=85) had a higher density of CD3 + TILs in association with more somatic mutations, higher neoantigen burden, and better survival compared to sporadic-MSI CRCs (n=67) (37). Recent analysis of cancer exomes in 18 cancer types found a correlation between survival outcomes and the overall burden of unstable microsatellites, suggesting that MSI may be more informative when analyzed as a continuous rather than a discrete phenotype (38).…”
Section: Discussionmentioning
confidence: 99%
“…he TIL density (CD3 + , CD4 + , CD8 + , and FOXP3 + T reg ) is prominent in MSI tumors relative to MSS tumors [31,53] and CD8 + and CD3 + , but not FOXP3, and TIL densities correlate well with the percentage of frameshift mutations detected in MSI tumors [54]. Among MSI mCRC cases, tumors in Lynch-associated patients show increased TIL infiltration (CD3 + , CD8 + , or T reg ) and higher TMB (median 384 vs. 71) compared to sporadic patients [55]. The quantification of T cells and cytotoxic T cells (CD3 and CD8) in mCRC tumors (immunoscore) shows that a higher immunoscore correlates with a decreased likelihood of metastasis [56] and can also predict overall survival [57].…”
Section: Immune Microenvironments In Crcmentioning
confidence: 99%